Communicable disease control and health protection handbook - Hawker, Jeremy; Begg, Norman T.; Blair, Iain; Reintjes, Ralf; Weinberg, Julius; Ekdahl, Karl (John Wiley & Sons, 2012)
This clear and concise text combines science with practical guidance for public-health physicians, epidemiologists, infection control nurses, microbiologists, and those training in these fields. It covers basic principles of communicable disease control and health protection, major syndromes, control of individual infections, main services and activities, organizational arrangements for all EU countries and sources of further information. All chapters have been updated in line with recent changes in epidemiology, new guidelines for control and administrative changes. New chapters on pandemic p.